A new species of the family Zetomotrichidae (Acari: Oribatida) from Iran - Mohammad Ali Akrami; Moslem Behmanesh (Persian Journal of Acarology)
Zetomotrichus persicus sp. nov., a new species of oribatid mites (Acari: Oribatida) of the family Zetomotrichidae, is described from Iran. The new species is recognized by the anteromedial rostral denticulation; long and filiform sensilla with 13 relatively long barbs on outer and four on inner sides; broad and pennate notogastral seta c2; pyriform organ with two anterolateral tubes; and absence of adanal seta ad3. An identification key to the known species of Zetomotrichus is given.